Physical fitness status modulates the inflammatory proteins in peripheral blood and circulating monocytes: role of PPAR-gamma - Antunes, Barbara Moura [UNESP]; Rosa-Neto, José Cesar; Batatinha, Helena Angélica Pereira; Franchini, Emerson; Teixeira, Ana Maria; Lira, Fábio Santos [UNESP] (Springer Nature, 2020)
The aim of this study was to analyze the metabolic and molecular profile according to physical fitness status (Low or High VO2max) and its impacts on peripheral and cellular inflammatory responses in healthy men. First (Phase I), inflammatory profile (TNF-α, IL-6, IL-10) was analyzed at baseline and post-acute exercise sessions performed at low (< 60% VO2max) and high (> 90% VO2max) intensities considering the individual endotoxin concentrations. Next (Phase II), monocyte cell cultures were treated with LPS alone or associated with Rosiglitazone (PPAR-γ agonist drug) to analyze cytokine production and gene expression. Monocyte subsets were also evaluated by flow cytometry. A positive relationship was observed between LPS concentrations and oxygen uptake (VO2max) (r = 0.368; p = 0.007); however, in the post-exercise an inverse correlation was found between LPS variation (Δ%) and VO2max (r = -0.385; p = 0.004). With the low-intensity exercise session, there was inverse correlation between LPS and IL-6 concentrations post-exercise (r = -0.505; p = 0.046) and a positive correlation with IL-10 in the recovery (1 h post) (r = 0.567; p = 0.011), whereas with the high-intensity exercise an inverse correlation was observed with IL-6 at pre-exercise (r = -0.621; p = 0.013) and recovery (r = -0.574; p = 0.016). When monocyte cells were treated with LPS, High VO2max individuals showed higher PPAR-γ gene expression whereas Low VO2max individuals displayed higher IL-10 production. Additionally, higher TLR-4, IKK1, and PGC-1α gene expression were observed in the High VO2max group than Low VO2max individuals. In conclusion, even with elevated endotoxemia, individuals with High VO2max exhibited higher IL-6 concentration in peripheral blood post-acute aerobic exercise and lower IL-10 concentration during recovery (1 h post-exercise). The anti-inflammatory effects linked with exercise training and physical fitness status may be explained by a greater gene expression of IKK1, TLR-4, and PGC-1α, displaying an extremely efficient cellular framework for the PPAR-γ responses.